2021
DOI: 10.3389/fphar.2021.632986
|View full text |Cite|
|
Sign up to set email alerts
|

Bryophyllum pinnatum Compounds Inhibit Oxytocin-Induced Signaling Pathways in Human Myometrial Cells

Abstract: Bryophyllum pinnatum has been used in the treatment of premature labor, first in anthroposophic hospitals and, recently, in conventional settings as an add-on medication. In vitro work with hTERT human myometrial cells showed that B. pinnatum leaf press juice inhibits the increase of intracellular free calcium concentration induced by oxytocin, a hormone known to play a role in labor. Our aim was to identify fractions/compounds in B. pinnatum press juice that contribute to this inhibitory effect, and to invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 35 publications
2
18
0
Order By: Relevance
“…Previous studies on rutin as a potent antioxidant and anti-urolithiatic agent have been well document by Enogieru, et al, (2018) and Ghodasara et al, (2010) respectively. Further, Radwan et al (2021) and Santos et al, (2021) have explored the possible role of the K. pinnata attributes in hemostasis and oxytocin signaling pathways respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies on rutin as a potent antioxidant and anti-urolithiatic agent have been well document by Enogieru, et al, (2018) and Ghodasara et al, (2010) respectively. Further, Radwan et al (2021) and Santos et al, (2021) have explored the possible role of the K. pinnata attributes in hemostasis and oxytocin signaling pathways respectively.…”
Section: Resultsmentioning
confidence: 99%
“…As pregnant women generally receive classical medication for various pathological situations, and at least one in five pregnant women consumes natural products simultaneously, the potential interactions between them must be considered [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The main bufadienolides present in the enriched fraction in both studies were bersaldegenin-1-acetate ( 13 ), bersaldegenin-3-acetate ( 14 ), bersaldegenin-1,3,5-orthoacetate ( 9 ), and bryophyllin A ( 7 ) [ 33 , 34 ]. A more recent study of the authors evaluated the effects of bioactive compounds from K. pinnata in the oxytocin signaling pathways in human myometrial cell cultures and showed that both bufadienolides and flavonoids take part in the cell events that lead to the inhibition of oxytocin signaling by K. pinnata leaf extracts [ 35 ]. The authors evaluated a bufadienolide-enriched fraction, a flavonoid-enriched fraction, and bersaldegenin-1,3,5-orthoacetate.…”
Section: Main Classes Of Bioactive Compounds In Kalanchoe ...mentioning
confidence: 99%
“…K. gracilis ) presenting a high content of flavonoids showed antioxidant, anti-inflammatory, and antiproliferative activities [ 58 ]. In some of these studies, the effect of the whole extract is higher than that of the fractions [ 35 , 58 ], indicating a synergistic effect of these compounds.…”
Section: Main Classes Of Bioactive Compounds In Kalanchoe ...mentioning
confidence: 99%